Moderasi Teologi Balā’ Dalam Tafsir Al-Amtsal Nashir Makarim Shiraz: Respon Atas Fatalisme Dan Eskapisme - Shodiq, Muhammad; Rahman, Chicha Putri; Nisa', Mauidlotun (Indonesia, 2023)
Fatalism and escapism are two human responses to the occurrence of balā' from two conflicting theological perspectives, namely the Ash'ariyah who view balā' as an absolute power of God, and the Mu'tazilah who view it as stemming from the absolute freedom of human action. Therefore, there is a need for a moderate mediating attitude between the two. This research aims to uncover the meaning of bala' in a moderate manner so as to provide a solution between fatalism and escapism. This research is a qualitative research with a thematic method and using a theological approach. The primary source of this article is the interpretation of the verses of balā' from Nasir Makarim Shirazi's perspective in Tafsir Al-Amthal, which tends to be moderate and tries to compromise the fatalist and escapist attitudes in responding to bala'. The research findings are that balā' in Nasir Makarim Shirazi's perspective is a means towards human development and perfection through efforts in his life so that his potentials will be seen and his abilities will be actualised. Balā' in the form of bad and good is a test of Allah. Nasir Makarim Shirazi divides the causes of balā' in humans into two. Firstly, because of God's will (irādah takwīniyah), which is based on the natural system he created. Secondly, it occurs due to the effects of man's actions on nature and his life, because balā' does not occur without man's own will and endeavours. From there, it can be concluded that humans are in a moderate and proportional position by not being fatalistic or escapist in their attitude when facing balā'